Pharmacological Studies on the Antidiabetic, Antioxidant, and Antimicrobial Efficacies of Commiphora myrrha Resin in Streptozotocin-Induced Diabetes in Rats: A Preclinical Study - Rasha A. Mansouri; Aftab Ahmad; null Roushdy M. M.; Huda F. Alshaibi; Mahmoud Ragab (Journal of Diabetes Research)
Background and Objectives. Commiphora myrrha resin is the traditionally used herbal remedy in the Middle East against a variety of diseases, including diabetes, due to its multiple pharmacological activities. The present study investigates the antioxidant, antimicrobial, and antidiabetic efficacies of aqueous extract of Commiphora myrrha resin (MAE) in streptozotocin-induced (STZ) diabetes in the female Sprague Dawley rats. Material and Methods. The thirty (30) female adult Sprague Dawley rats were randomly and equally segregated into three sets of experimental groups: group I (normal control): the rats were given an intraperitoneal injection of sodium citrate buffer solution and marked as a normal control group (NCG); group II (diabetic control): the rats were injected with STZ (60 mg/kg body weight (b.w.)) and marked as the diabetic control group (DCG); and group III (MAE treated): the rats were injected with STZ (60 mg/kg b.w.) for induction of diabetes and treated with MAE powder (0.5 mL of 0.5 g/kg b.w.) dissolved in distilled water. The treatment was given for 30 days. All rats were sacrificed after 30 days of treatment. The blood samples from each rat were collected for biochemical analysis, and the pancreas was taken for histopathological examination. Results. The aqueous extracts of MAE were phytochemically analyzed, and the results revealed the presence of high concentrations of tannins, sterols, and isoprenoids (terpenoids), while steroids and flavonoids were found in moderate concentrations. The plant extract showed promising inhibition of the growth of gram-positive and gram-negative pathogens. It also showed that MAE has potential antihyperglycemic and antioxidant activities. Microscopic examination of the pancreas showed degenerative changes and atrophy associated with dilatation of the exocrine ducts in the STZ-induced diabetic rats, while the treatment revealed that the Langerhans islets were close to normal without any histopathological alteration. Conclusion. The present results suggested that an aqueous extract of MAE could be considered an efficient antidiabetic, antioxidant, and antimicrobial treatment in the future.